Paciente masculino de 68 años con cáncer gástrico - Gómez Ríos, Jamaly Leticia (2019)
The present clinical case study is based on a 68-year-old male patient who was diagnosed with gastric cancer as well as his father and brother who died of this cause. He came to the clinic for presenting upper gastrointestinal bleeding expressed by repeated hematemesis. and hair with abundant blood loss of approximately one liter that is accompanied by abdominal pain, adynamia, pallor and weight loss. The patient is given a comprehensive nutritional assessment and is determined through the body mass index that presents low weight with mild energy deficiency and mild malnutrition. On the other hand, biochemical tests were performed in which his results reflect anemia due to decreased values of red blood cells. , hemoglobin and hematocrit and the decrease in albumin values is due to the fact that there is a mild depletion, when the physical examination shows generalized pallor, due to the advanced stage of the cancer, a feeding plan must be made by parenteral nutrition as long as the gastrointestinal tract not functional and implement the administration of iron and vitamin C to reverse the anemia, then to recover the gastrointestinal tract with the disappearance of the bleeding will continue with enteral nutrition, through monitoring and monitoring that is done to the patient his weight increased 2 kilos, whereby an improvement is seen in the patient, his biochemical tests were raised but anemia still exists, in a critical oncological patient the energy requirements are: proteins of 1.5 to 2.5 g / kg / day, carbohydrates of 3 to 5 g / kg / day and lipids 1 g / kg / day.